Heart failure induced by isoproterenol: A comparison of two doses and two delivery methods in C57BL/6J mice - Yaojiang Wang; Rong Yang; Aonan Yu; Peng Yang; Shaojie Huang; Yuqing Ye; Chunxiao Zhu; Mengxiao Zhang (PLoS ONE, 2025)
Heart failure (HF) modeling requires standardized protocols to ensure translational relevance. Despite the widespread use of isoproterenol (ISO)—a β-adrenergic agonist—in HF modeling, methodological inconsistencies in dosing and administration routes limit reproducibility. This study evaluated the effects of subcutaneous (SC) and intraperitoneal (IP) administration of ISO at two literature-established doses (5 and 60 mg/kg/day for 14 days) on cardiac remodeling in C57BL/6J mice, aiming to identify the optimal protocol for HF modeling. Using a factorial design, male C57BL/6J mice aged 6–8 weeks were divided into six cohorts: (1) SC saline control, (2) IP saline control, (3) SC 5 mg/kg ISO, (4) IP 5 mg/kg ISO, (5) SC 60 mg/kg ISO, and (6) IP 60 mg/kg ISO, with daily administration for 14 days. High-dose ISO (60 mg/kg/day) induced a 25% mortality rate in both SC and IP cohorts, yet IP administration exhibited marked inter-individual variability, undermining model reliability. Echocardiography revealed SC 5 mg/kg group induced stable systolic dysfunction accompanied by left ventricular dilation, while maintaining 100% survival. This cohort also displayed significantly elevated hypertrophy indices. Histopathological quantification suggested that SC 60 mg/kg induced extensive fibrosis. All ISO-treated groups showed upregulated myocardial hypertrophy markers and approximately 2-fold elevation in serum NT-proBNP levels. In summary, SC 5 mg/kg/day regimen not only ensures reliable phenotype induction but also reduces animal attrition, offering a robust platform for investigating CHF mechanisms and accelerating therapeutic development.